Early operative management in patients with adhesive small bowel obstruction: population‐based cost analysis. Issue 5 (30th June 2020) - Behman, R.; Nathens, A. B.; Pechlivanoglou, P.; Karanicolas, P.; Jung, J.; Look Hong, N.
Abstract : Background: Adhesive small bowel obstruction (aSBO) is a potentially recurrent disease. Although non‐operative management is often successful, it is associated with greater risk of recurrence than operative intervention, and may have greater downstream morbidity and costs. This study aimed to compare the current standard of care, trial of non‐operative management (TNOM), and early operative management (EOM) for aSBO. Methods: Patients admitted to hospital between 2005 and 2014 in Ontario, Canada, with their first episode of aSBO were identified and propensity‐matched on their likelihood to receive EOM for a cost–utility analysis using population‐based administrative data. Patients were followed for 5 years to determine survival, recurrences, adverse events and inpatient costs to the healthcare system. Utility scores were attributed to aSBO‐related events. Cost–utility was presented as the incremental cost‐effectiveness ratio (ICER), expressed as Canadian dollars per quality‐adjusted life‐year (QALY). Results: Some 25 150 patients were admitted for aSBO and 3174 (12·6 per cent) were managed by EOM. Patients managed by TNOM were more likely to experience recurrence of aSBO (20·9 per cent versus 13·2 per cent for EOM; P < 0·001). The lower recurrence rate associated with EOM contributed to an overall net effectiveness in terms of QALYs. The mean accumulated costs for patients managed with EOM exceeded those of TNOM (17 951 versus 11 594 (€12 288 versus €7936) respectively; P < 0·001), but the ICER for EOM versus TNOM was 29 881 (€20 454) per QALY, suggesting cost‐effectiveness. Conclusion: This retrospective study, based on administrative data, documented that EOM may be a cost‐effective approach for patients with aSBO in terms of QALYs. Future guidelines on the management of aSBO may also consider the long‐term outcomes and costs. Abstract : This population‐based cost–utility analysis compared early operative management (EOM) for adhesive small bowel obstruction (SBO) to the current standard of care of a trial of non‐operative management. Although EOM was more costly, it was associated with a significantly lower risk of recurrence and reduced exposure to the morbidity and costs associated with multiple admissions for adhesive SBO. With longer follow‐up, EOM becomes increasingly cost‐effective, and crosses published willingness‐to‐pay thresholds within 5 years of the first admission. Early operative management in small bowel occlusion Abstract : Antecedentes: La oclusión de intestino delgado por adherencias ( adhesive small bowel obstruction, aSBO) es una enfermedad potencialmente recidivante. Aunque el tratamiento no quirúrgico es a menudo eficaz, se asocia con un mayor riesgo de recidiva que la intervención quirúrgica, y puede provocar más adelante morbilidad y costes. El objetivo de este estudio fue comparar un Ensayo de Tratamiento No Quirúrgico ( Trial of Non‐operative Management, TNOM, el estándar actual de tratamiento) con Tratamiento Operatorio Precoz ( Early Operative Management, EOM) para el tratamiento de aSBO. Métodos: Pacientes ingresados en el hospital entre 2005‐2014 en Ontario, Canadá con un primer episodio de aSBO fueron identificados y emparejados por puntaje de propensión respecto a la probabilidad de recibir EOM para un análisis de coste‐utilidad utilizando datos administrativos de base poblacional. Los pacientes fueron seguidos durante 5 años para determinar la supervivencia, recidivas, eventos adversos, y costes de la hospitalización para el sistema de salud. Las puntuaciones de utilidad se atribuyeron a los eventos relacionados con la aSBO. El coste‐utilidad se presentó como la razón costo efectividad incremental ( incremental cost‐effectiveness ratio, ICER) expresada como dólares por año de vida ajustado por calidad ( quality‐adjusted life‐year, QALY). Resultados: Un total de 25.150 pacientes fueron ingresados por aSBO y 3.174 (12, 6%) fueron tratados con EOM. Los pacientes tratados mediante TNOM tenían más probabilidades de presentar una recidiva de la aSBO (20, 9% versus 13, 2%, P < 0, 0001). La menor incidencia de recidivas asociada con EOM contribuyó a una eficacia neta global en términos de QALYs. Mientras que los costes medios acumulados para los pacientes tratados con EOM superaron a los de TNOM (17, 951 versus 11, 594, P < 0, 0001), el ICER de EOM versus TNOM fue 29, 881/QALY, lo que sugiere un coste‐eficacia de esta estrategia. Conclusión: Este estudio retrospectivo basado en datos administrativos evidenció que EOM puede representar un abordaje coste‐efectivo para pacientes con aSBO en términos de QALYs. Las futuras guías clínicas para el tratamiento de la aSBO pueden también considerar los resultados a largo plazo y los costes.